Efficient eradication of organotin utilizing K2FeO4 augmented by nZVI: revelations on influential factors, kinetic dynamics, and mechanistic insights - Huang, Yuanyuan; Yang, Qingwei; Song, Ling; Ran, Hongjie; Jiang, Hui; Sun, Da (Frontiers in Environmental Science, 2024)
In this study, we investigated the oxidative mechanisms of nano zero-valent iron (nZVI) enhanced potassium ferrate (K2FeO4), focusing on tributyltin (TBT) and triphenyltin (TPhT) as target pollutants. The addition of nZVI enhanced the degradation of both organic tin compounds by K2FeO4, exhibiting pseudo-first-order kinetics influenced by pH, carbonate, and fulvic acid. nZVI, as a reducing agent, facilitated the generation of stronger oxidizing species Fe (V) and Fe (IV) from K2FeO4 through electron transfer. The presence of hydroxyl radicals (•OH) was confirmed by tert-butyl alcohol (TBA) verification. Intermediate products of TBT degradation by nZVI-enhanced K2FeO4 were identified using GC-MS, confirming de-alkylation leading to stepwise oxidation to inorganic tin ions. Due to excessively long Sn-C bonds in diphenyltin, rendering them unstable, Density Functional Theory (DFT) calculations were employed. Results indicated that Fe (IV) and Fe (V) predominantly attacked the Sn-C bonds of TPhT, while •OH primarily targeted the benzene ring. HOMO energy levels suggested that Fe(V) was more prone to oxidizing TPhT than Fe (IV). Gibbs free energy calculations demonstrated that, in the presence of Fe (IV) and Fe (V), the energy barrier for breaking bonds and oxidizing into inorganic tin ions decreased, favoring the process over the self-decomposition of TPhT. Additionally, the lower energy barrier for •OH indicated an easier degradation of TPhT. This study reveals that nZVI-enhanced K2FeO4 effectively removes TBT and TPhT, contributing to the understanding of the ferrate-mediated degradation mechanism of organic tin compounds. The findings offer insights and theoretical guidance for remediating organic tin pollution in aquatic environments.